The inhibition of antigen-presenting activity of dendritic cells resulting from UV irradiation of murine skin is restored by in vitro photorepair of cyclobutane pyrimidine dimers - Vink, Arie A. (The National Academy of Sciences of the USA, 1997)
Exposing skin to UVB (280–320 nm) radiation suppresses contact hypersensitivity by a mechanism that involves an alteration in the activity of cutaneous antigen-presenting cells (APC). UV-induced DNA damage appears to be an important molecular trigger for this effect. The specific target cells in the skin that sustain DNA damage relevant to the immunosuppressive effect have yet to be identified. We tested the hypothesis that UV-induced DNA damage in the cutaneous APC was responsible for their impaired ability to present antigen after in vivo UV irradiation. Cutaneous APC were collected from the draining lymph nodes of UVB-irradiated, hapten-sensitized mice and incubated in vitro with liposomes containing a photolyase (Photosomes; Applied Genetics, Freeport, NY), which, upon absorption of photoreactivating light, splits UV-induced cyclobutane pyrimidine dimers. Photosome treatment followed by photoreactivating light reduced the number of dimer-containing APC, restored the in vivo antigen-presenting activity of the draining lymph node cells, and blocked the induction of suppressor T cells. Neither Photosomes nor photoreactivating light alone, nor photoreactivating light given before Photosomes, restored APC activity, and Photosome treatment did not reverse the impairment of APC function when isopsoralen plus UVA (320–400 nm) radiation was used instead of UVB. These controls indicate that the restoration of APC function matched the requirements of Photosome-mediated DNA repair for dimers and post-treatment photoreactivating light. These results provide compelling evidence that it is UV-induced DNA damage in cutaneous APC that leads to reduced immune function.